Dynamic Allocation Strategy for the Car Rental Industry with Multiple Rental Channels: Dynamic Allocation Strategy for the Car Rental - Peng-Sheng You; Yi-Chih Hsieh (International Journal of Engineering and Technology Innovation, 2025)
This paper addresses the rental car allocation problem in which a car rental company rents its cars through various channels. This study proposes a constrained model based on the nested-allocation structure to allocate the rental cars to the car rental system to maximize the total rental revenues. The nested allocation strategy uses the concept of whether the number of sales accumulated to a certain level exceeds a threshold corresponding to that sharer. This approach allows the quota of low-profit channels to support the leasing demand of high-profit channels at any time, thereby increasing revenue. The proposed model can dynamically adjust the nested strategy as the dynamic programming model. However, it avoids the issues of ample storage space and long calculation time commonly encountered by the dynamic programming model. Computational results show that the proposed nested approach substantially outperforms the traditional exclusive allocation approach.